A STRUGGLE FOR SAVING THE WORLD BY CAPTAIN STEVEN HILLER IN INDEPENDENCE DAY MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WIDYANINGRUM , DIAN (2010)
The major problem of this study is to reveal the struggle of saving the world by Steven Hiller reflected in Independence Day movie. The objectives of the study are; to analyze the structural elements of the movie and to analyze the character of Steven Hiller based on individual psychological analysis. This study belongs to qualitative study. In this method, there are two types of data sources, which are used, namely primary data and secondary data sources. The primary data source is the movie Independence Day, meanwhile the secondary data source are the other sources related to the analysis such as internet, books and other references which are related to this study. The result of the research shows that the character of Steven Hiller has some struggles for saving the earth from alien that attack the earth. With his obsession and team work finally the aliens can be destroyed